2007
DOI: 10.1021/ie061688c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micropollutants (Organic Xenobiotics and Heavy Metals) on the Activated Sludge Process

Abstract: Four experiments were performed in sequencing batch reactors, two by two in parallel, to study the effect of micropollutants (organic xenobiotics and heavy metals) on the performance of activated sludge processes. The reactors were operated for long times (at least 11 months each) and in a wide range of sludge ages (5-30 days). It was observed that production of biological solids, COD removal, and settling properties were not affected by the presence of micropollutants significantly. On the other hand, ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Biological treatments are designed to remove the organic matter and nutrients in wastewater and not necessarily to remove heavy metals; only a side benefit can be observed in the treatment of heavy-metal-bearing streams [41]. In this study, removal of Cr, Hg, and Pb was observed in all WWTPs, with the removal efficiency of 55.95%-92.5%, 37.87%-88.03%, and 8.7%-63.11%, while the removal of As and Cd was only achieved in some WWTPs, unsteadily.…”
Section: Heavy Metal Risk Of the Treated Effluentmentioning
confidence: 99%
“…Biological treatments are designed to remove the organic matter and nutrients in wastewater and not necessarily to remove heavy metals; only a side benefit can be observed in the treatment of heavy-metal-bearing streams [41]. In this study, removal of Cr, Hg, and Pb was observed in all WWTPs, with the removal efficiency of 55.95%-92.5%, 37.87%-88.03%, and 8.7%-63.11%, while the removal of As and Cd was only achieved in some WWTPs, unsteadily.…”
Section: Heavy Metal Risk Of the Treated Effluentmentioning
confidence: 99%
“…1 and 2, xenobiotics concentration is in the mg L −1 range in industrial wastewaters and in the μg L −1 in municipal ones. The different xenobiotics concentration in industrial and municipal wastewaters poses different challenges to biodegradation processes: very low concentrations of xenobiotics will cause a very slow microbial growth or might not be able to sustain growth at all; higher concentrations should give higher biodegradation rates and should be able to sustain microbial growth but inhibitory effects, e.g., on nitrification 21, might be possible.…”
Section: Presence Of Xenobiotics In Wastewatersmentioning
confidence: 99%
“…Discharge of untreated petroleum refinery wastewater containing nickel into water bodies results in environmental and human health problems [5]. Accumulation of nickel in the body can cause lung fibrosis, cardiovascular, kidney diseases and act as carcinogenic agent [8][9][10]. Excessive concentrations of nickel in water affect the living organism's growth such as algae [10].…”
Section: Introductionmentioning
confidence: 99%